The mirror effect: seeing and being seen in the cult of María Lionza (Venezuela). Issue 2 (3rd April 2018) - Canals, Roger
Abstract : In the cult of María Lionza (Venezuela), the look or gaze constitutes a fundamental aspect of the ritual process, since it is one of the privileged ways through which the relations between spirits, mediums and participants are established. The use of the camera as a research method helps to gain a better understanding of this issue, since the action of holding a camera – and looking through it – may provoke comments and reactions among believers, resulting in a process by which a set of assumptions about the meaning of seeing and being seen that usually remain implicit become explicit. Most of the time, these newly explicit assumptions appear as visual prohibitions or as a consequence of a mistake made by the researcher. What I defend in this paper is that 'visual mistakes' and prohibitions are very valuable in anthropological research and should be taken into account. The text concludes with two general reflections: one about the connection between cinema and the sacred, and the other about the intimate relationship between what we usually call 'theory' and 'practice' in visual anthropology.